Changing paradigm of sacral neuromodulation and external anal sphincter repair for faecal incontinence in specialist centres. (22nd September 2020) - Ong, K.; Bordeianou, L.; Brunner, M.; Buntzen, S.; Collie, M.H.S.; Hanly, A.; Hunt, C. W.; Matzel, K. E.; O'Connell, P. R.; Rydningen, M.; Savitt, L.; Totaro, A.; et al.
Abstract: Aim: The aim of this study was to determine whether the paradigm of surgical intervention for faecal incontinence (FI) has changed between 2000 and 2013. Method: This was a multi‐centre retrospective study of patients who had undergone either sacral neuromodulation (SNM) or delayed sphincter repair or sphincteroplasty (SR) as a primary surgical intervention for FI in five centres in Europe and one in the United States. The flow of patients according to the intervention, sustainability of the treatment at a minimum follow‐up of 5 years, complications and requirement for further interventions were recorded. Results: A total of 461 patients (median age 56 years, range 24–90 years, 41 men) had either SNM or SR as an index operation during the study period [SNM 284 (61.6%), SR 177 (38.4%)]. Among SNM patients, there were 169 revisional operations (change of battery and/or lead, re‐siting or removal). At the time of last follow‐up 203 patients (71.4%) continued to use SNM. Among SR patients, 30 (16.9%) had complications, most notably wound infection (22, 12.4%). During follow‐up 32 patients (18.1%) crossed over to SNM. Comparing two 4‐year periods (2000–2003 and 2007–2010), the proportion of patients operated on who had a circumferential sphincter defect of less than 90° was 48 (68%) and 45 (46%), respectively ( P = 0.03), while those who had SNM as the primary intervention increased from 29% to 89% ( P < 0.05). Conclusion: The paradigm of surgical intervention for FI has changed with increasing use of SNM.